2020
DOI: 10.1155/2020/8879758
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum and Gene Expression of Galectin-4, Interleukin-27, and Complement-7 in Hepatitis C Virus-Infected Egyptian Patients

Abstract: Background. Hepatitis C virus (HCV) is considered a major global public health problem. Recently, there are great advances in HCV therapy, but there are some limitations that are creating an urgent need for assessment of some cytokines that have a potent antiviral effect in the immune system and anti-inflammatory effects to provide a potential novel immunotherapeutic target in HCV infection. Objective. This study was directed to assess the serum levels and gene expression levels of Galectin-4 (LEG4), Interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In our study, the outcome of PCV3 inoculation to CDCD piglets indicates PCV3 infection cannot induce obvious clinical symptoms and pathological changes. The appearance of clinical symptoms and the severity of the disease may be affected by the immune status of pigs [ 38 , 39 ], stress factors that cause systemic inflammation [ 40 , 41 ], or coinfection with other pig pathogens [ 42 , 43 ]. The cumulative results in our study demonstrated that PCV3 trend to low pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the outcome of PCV3 inoculation to CDCD piglets indicates PCV3 infection cannot induce obvious clinical symptoms and pathological changes. The appearance of clinical symptoms and the severity of the disease may be affected by the immune status of pigs [ 38 , 39 ], stress factors that cause systemic inflammation [ 40 , 41 ], or coinfection with other pig pathogens [ 42 , 43 ]. The cumulative results in our study demonstrated that PCV3 trend to low pathogenicity.…”
Section: Resultsmentioning
confidence: 99%
“…Galectins were shown to bind viral glycans and PRR extracellularly and interact with viral and cytosolic components present in the cytoplasm and therefore, might be able to modulate immune responses [57][58][59]. Furthermore, increased galectin levels, and in particular galectin-9 levels, were observed upon viral infections [60] to dengue [61], influenza [62], HIV [63], hepatitis B and C [64,65] as well as COVID-19 [66] as compared to healthy controls. Furthermore, recent studies have suggested the use of plasma concentrations of galectins as biomarkers for disease prognosis since elevated plasma galectins were linked to higher viral load or more severe infection.…”
Section: Discussionmentioning
confidence: 99%